2018
DOI: 10.1007/s00394-018-1784-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota, dietary intakes and intestinal permeability reflected by serum zonulin in women

Abstract: PurposeIncreased gut permeability causes the trespass of antigens into the blood stream which leads to inflammation. Gut permeability reflected by serum zonulin and diversity of the gut microbiome were investigated in this cross-sectional study involving female study participants with different activity and BMI levels.Methods102 women were included (BMI range 13.24–46.89 kg m−2): Anorexia nervosa patients (n = 17), athletes (n = 20), normal weight (n = 25), overweight (n = 21) and obese women (n = 19). DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 60 publications
1
67
1
4
Order By: Relevance
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the severity and activity of chronic health conditions including liver disease, metabolic syndrome, PCOS, coeliac disease and BMI were reported to correlate with the degree of IP. The notion that IP correlates with disease severity is further supported as the severity of particular risk factors also increase alongside the degree of IP . The involvement of IP in chronic disease, especially with advanced disease severity, highlights the potential importance of intestinal integrity in health and disease.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations